Bibliographic review: Applications and recommendations on the use of magnetic resonance imaging in the management of ischemic heart disease (Research, Society and Development, 2023)
The study focuses on the applications of magnetic resonance imaging (MRI) in the context of ischemic heart disease and evaluates its accuracy as a diagnostic method. Searches were carried out on PubMed, EBSCO and Medline, in addition to consulting data from the Brazilian Ministry of Health. Ischemic heart disease is one of the main causes of morbidity and mortality worldwide, mainly affecting people between 60 and 69 years old, with a higher incidence in men, especially in the southeastern region of Brazil. It presents a wide pathological and clinical spectrum, such as angina pectoris, acute myocardial infarction and ischemic cardiomyopathy. In this sense, MRI plays a crucial role in the diagnosis and prognosis of ischemic heart disease. It allows you to evaluate ventricular function, identify areas with low perfusion, characterize areas with necrosis and fibrosis and determine the accuracy of myocardial tissue. It is also used to assess myocardial perfusion, using vasodilatory medications to detect pathological abnormalities. It was studied that the diagnostic accuracy of MRI in the context of ischemic heart disease, considering the different techniques available, is high and satisfactory. In addition to diagnosis, MRI also plays a prognostic role, with patients with normal results having fewer cardiac events over time. Therefore, MRI plays a crucial role in the evaluation of ischemic heart disease, offering significant advantages in terms of diagnosis and prediction compared to other imaging methods. It allows you to evaluate cardiac function, identify areas with perfusion deficiency and characterize affected tissues, making it a useful tool in the treatment and monitoring of these cardiovascular conditions.